Hyperventilation Therapy for Control of Posttraumatic Intracranial Hypertension - Godoy, Daniel Agustín; Seifi, Ali; Garza, David; Lubillo-Montenegro, Santiago; Murillo-Cabezas, Francisco (Frontiers in Neurology, 2017)
During traumatic brain injury, intracranial hypertension can become a life-threatening condition if it is not managed quickly and adequately. Physicians use therapeutic hyperventilation to reduce elevated intracranial pressure (ICP) by manipulating autoregulatory functions connected to cerebrovascular CO2 reactivity. Inducing hypocapnia via hyperventilation reduces the partial pressure of arterial carbon dioxide (PaCO2), which incites vasoconstriction in the cerebral resistance arterioles. This constriction decrease cerebral blood flow (CBF), which reduces cerebral blood volume (CBV) and, ultimately, decreases the patient’s ICP. The effects of therapeutic hyperventilation are transient, but the risks accompanying these changes in cerebral and systemic physiology must be carefully considered before the treatment can be deemed advisable. The most prominent criticism against this approach is the cited possibility of developing cerebral ischemia and tissue hypoxia. While it is true that certain measures, such as cerebral oxygenation monitoring, are needed to mitigate these dangerous conditions, using available evidence of potential poor outcomes associated with hyperventilation as justification to dismiss the implementation of therapeutic hyperventilation is debatable and remains a controversial subject among physicians. This review highlights various issues surrounding the use of hyperventilation as a means of controlling posttraumatic intracranial hypertension, including indications for treatment, potential risks and benefits, and a discussion of what techniques can be implement to avoid adverse complications.